Drug Enforcement Administration Rescheduling of Hydrocodone Combination Products Is Associated With Changes in Physician Pain Management Prescribing Preferences. (3rd April 2019) - Fleming, Marc L.; Driver, Larry; Sansgiry, Sujit S.; Abughosh, Susan M.; Wanat, Matthew A.; Varisco, Tyler J.; Pickard, Todd; Reeve, Kathleen; Todd, Knox H.
Abstract: Due to rising misuse, the Drug Enforcement Administration (DEA) moved hydrocodone combination products (HCPs) from DEA Schedule III to DEA Schedule II in October 2014. Aside from increasing regulatory scrutiny, rescheduling may have increased the administrative burden surrounding HCP prescribing. This study explored how HCP rescheduling and associated administrative barriers may have affected physician treatment of acute (aNCP) and chronic (cNCP) noncancer pain. To this end, physician members of the Texas Medical Association completed a self-administered online questionnaire. Pharmacotherapy treatment plan was measured with two questions asking physicians whether they were more likely to recommend HCPs, acetaminophen/codeine (APAP/codeine), nonsteroidal anti-inflammatory drugs (NSAIDs), tramadol, or other agents for the treatment of aNCP and cNCP. Two Likert-scaled items were used to assess administrative burden. In total, 1365 physicians responded (response rate = 15.39%). Physicians more frequently selected APAP/codeine (37%) for aNCP and tramadol (44%) for cNCP. A majority (78.8%) of physicians agreed that rescheduling led to modified prescribing, and those in agreement were significantly less likely than those who disagreed to prescribe HCPs for aNCP (24.2% vs. 56.4%; χ 2 = 68.6, P < .001) and cNCP (16.9% vs. 37%; χ 2 = 36.1, P < .001). Rescheduling and associated administrative burden are both associated with modified physician HCP prescribing in both aNCP and cNCP.